2016
DOI: 10.1186/s12879-016-2042-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of and risk factors for neonatal candidemia at a tertiary care hospital in western China

Abstract: BackgroundThe prevalence and clinical characteristics of neonatal candidemia are poorly understood in western China. The aim of our study was to evaluate the epidemiological features of neonatal candidemia in the Liuzhou Maternity and Child Healthcare Hospital.MethodsA retrospective case-control study was conducted between January 2012 and November 2015. Electronic databases were reviewed and data on Candida species were isolated from blood cultures and candidemia incidence, risk factors, and mortality were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
2
9
1
3
Order By: Relevance
“…In the present study, the prevalence of 14.7% for fungal sepsis is similar to the rates of 11%, 13.6%, 13.9% and 11.97% reported by Rani et al, (28), Agarwal et al, (29), Chen et al, (30) and Chavhan et al, (27) respectively. In a previous study by Mokhtar et al,(11), the rate of fungal neonatal sepsis reported was 12% of the total diagnosed cases while bacterial sepsis represented 88%, but in the current study, fungal sepsis has increased to 14.7%.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the prevalence of 14.7% for fungal sepsis is similar to the rates of 11%, 13.6%, 13.9% and 11.97% reported by Rani et al, (28), Agarwal et al, (29), Chen et al, (30) and Chavhan et al, (27) respectively. In a previous study by Mokhtar et al,(11), the rate of fungal neonatal sepsis reported was 12% of the total diagnosed cases while bacterial sepsis represented 88%, but in the current study, fungal sepsis has increased to 14.7%.…”
Section: Discussionsupporting
confidence: 91%
“…Because of their immature immune system, neonates are particularly vulnerable to invasive candidemia. Incriminated factors include prolonged endotracheal intubation, total parenteral nutrition (TPN), indwelling venous catheterization, and broad-spectrum antibiotics (3). While Candida albicans has long been accountable for the major-ity of candidemia cases, non-albicans Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…La tasa de incidencia hospitalaria de Candida en el estudio fue de 20 por cada 1.000 admisiones, siendo elevada al compararse con otros estudios como el de Feja et al 6 en Nueva York, Fu et al 9 y Chen et al 10 en China y Pinhat et al 11 en Brasil siendo 15.9, 13.6, 10.6 y 9.0 por cada 1.000 admisiones respectivamente. Dentro de las posibles razones asociadas a la elevada incidencia de candidemia en nuestra institución, se pueden mencionar: el hacinamiento diario (censo por arriba de la capacidad), el poco personal médico y de enfermería (relación numérica por paciente), la alta complejidad de las patologías, ser un centro de referencia nacional y el uso indiscriminado de antibióticos de amplio espectro.…”
Section: Discussionunclassified
“…El 49% de los casos de candidemia fue causado por Candida parapsilosis similar a lo expuesto en los estudios Yu et al 12 , Rodríguez et al 13 , Neu et al 14 , Celebi et al 15 y Caggiano et al 16 A diferencia, otros estudios, Feja et al 6 , J. Fu et al 9 , Chen et al 10 , Saiman et al 17 , Robinson et al 18 , Juyal et al 19 , Hsu et al 20 y Márquez et al 21 , donde se describe que la especie de predominio fue Candida albicans.…”
Section: Discussionunclassified
See 1 more Smart Citation